Ancient waters installations in the land area of YaḥṢb archeological remains Dam Al-Raqud a model - Al-Wajih, Maher Abdullah Dabwan (Jordan Journal for History and Archaeology, 2025)
The research deals with one of the most important archaeological dams built by the Himayris in a relatively high mountainous area located close to the fertile agricultural bottom, which is currently known as the bottom of the field (Qaa- al-Hqal). This dam has remained an unidentified period of time, and many people are unknown after the use of the use of it as a result of the transformation of the storage lake into an agricultural field filled with fertile grazing soil, which is still being swept away by torrents with its annual flow in the seasons of heavy rains. The field study showed that this dam was playing a dual functional role (dual -function); It is a temporary storage of torrential water by reserving it behind the dam’s body until the time of need. This dam was designed so that it can redirect the surplus from the storage lake directly to the agricultural fields under the dam. Here, for the first time, an archaeological dam was recognized in the first place with the purpose of quarrels in agricultural terraces built on a mountain foot that overlooks the valley of Wadi Di Ḥaryim, one of the tributaries of Wadi Banna.